Youth and digital technologies. Diagnosis of the use and appropriation of digital platforms in the conurbation area of southern Tamaulipas - Lemus-Pool, María Consuelo (Universidad Autónoma de Tamaulipas, 2020)
In Mexico, several studies exist about what young people do on the web and how they interact in these environments; however, concerning southern Tamaulipas, there are no specific studies that address the characteristics of these practices. The objective of this work is to present a diagnosis of the uses and appropriations of digital platforms among young people in the southern region of Tamaulipas, Mexico, among high school and college students. The methodology is quantitative, based on a descriptive non-experimental design. A statistically representative sample from the municipalities of Tampico, Ciudad Madero, and Altamira, was designed with a 95 % accuracy and a margin  of error of +/- 2 %. A questionnaire was developed and administered to a sample of 1 222 young students, in which the intensity of use and navigation profile of various digital platforms was evaluated. These platforms include general information pages, information or product exchange, digital social networks, educational and learning sites, as well as entertainment. The findings show that two fundamental elements mediate the processes of use  and appropriation of digital platforms: a technical component, related to the interactivity resources provided by the platform itself, and a socio cultural component that relates to the life story, social and cultural capital, personality and expressive capacity, as well as the digital skills and intrinsic motivations of young people. In conclusion, this study allows us to problematize the phenomenon of the appropriation of digital platforms from the local level and to propose intervention routes that take advantage of the identified potential of digital skills, collaboration and content production.